On the Dirichlet problem for quasilinear Poisson equations - Gutlyanskii, V.Ya.; Nesmelova, O.V.; Ryazanov, V.I. (Праці Інституту прикладної математики і механіки НАН України, 2017)
We study the Dirichlet problem for the quasilinear partial differential equations of the form Δu(z) = h(z)·f(u(z)) in the unit disk D ⊂ C with functions h : D → R in the class Lp(D), p > 1, and continuous functions f : R → R with nondecreasing |f | of |t| such that f(t)/t → 0 as t → ∞.